TOOLPATH GENERATION AND OPTIMIZATION OF MACHINING OF PINE WOOD SURFACES (Innovation in Woodworking Industry and Engineering design, 2026)
In this paper are presented methods for wood working milling machining, specially we aregoing to use samples of pine wood. In the beginning a sculpture surfaces will be designed in aCAD/CAM software Fusion 360 and tool paths will be generated using four different strategiesfor finishing stage, these are: a) parallel, b) scallop, c) radial and d) pencil. On the upper machiningsurface of the final physical parts we measure the roughness in order to check the producedquality for each strategy. Each strategy compared according the total machining time,the cutting conditions and the geometric accuracy. Physical models will be produced with theuse of a rapid prototyping machine ROLAND MDX- 40A for evaluation and tool path comparison.